Implementation of Evidence-Based Cervical Ripening Protocol: Outcomes and Next Steps - Arthurine Zakama; Nasim C. Sobhani; Robyn Lamar; Melissa G. Rosenstein (Thieme Medical Publishers, Inc., 2020)
Objective A prominent randomized controlled trial demonstrated that low-dose misoprostol with the concurrent cervical Foley shortened the median time to delivery when compared with either method alone. Our study aims to address implementation of this protocol and evaluate its impact on time to delivery. Study Design This was a retrospective before-and-after study of nulliparous women who delivered nonanomalous, term, singletons at the University of California San Francisco (UCSF) in two separate 2-year periods before and after changes in UCSF's cervical ripening protocol. The primary outcome was time from first misoprostol dose to delivery. Results A total of 1,496 women met inclusion criteria, with 698 in the preimplementation group and 798 in the postimplementation group. There were no statistically significant differences in time to delivery (29 vs. 30 hours, p = 0.69), rate of cesarean delivery (30 vs. 26%, p = 0.09), or cesarean delivery for fetal indications (11 vs. 8%, p = 0.15) between the groups. Conclusion Implementing evidence-based low-dose misoprostol with the concurrent cervical Foley did not change the time to delivery, time to vaginal-delivery, or likelihood of vaginal delivery in our population. This may be due to differences in labor management practices and incomplete fidelity to the protocol. Real-world effectiveness of these interventions will vary and should be considered when choosing an induction method.